Analysis of Determinants of Hypertension Potential Stroke Incidence in Health Center Work Areas in Manggarai Regency - Wea, Lidwina (NurseLine Journal, 2026)
Background: Stroke is still the leading cause of death for sufferers. One of the risk factors for stroke is hypertension. Hypertension remains the most prevalent disease among people in Pagal, Cibal District, Manggarai. The most effective way to reduce the burden of stroke is to know the risk factors other than hypertension such as age, family history of stroke, diabetes mellitus, cholesterol levels, smoking, weight, physical activity, and history of heart disease. Objectives: This study aims to identify factors associated with stroke risk, which can inform strategies to improve overall health and reduced the risk of stroke. Method: This study is a quantitative descriptive study, conducted in the working area of ​​the Pagal Health Center, Manggarai Regency. A total of 60 respondents, consisting of 19 men and 41 women, who are hypertensive patients, were involved. Respondents were identified using inclusion criteria. The sample selection approach used was purposive, namely the selection of samples by considering certain criteria such as being 45-59 years old or pre-elderly age who experience hypertension. The questionnaire assessed stroke risk factors consisting of 9 indicators. The researcher conducted univariate tests of the participants' characteristics and risk factors for stroke for the data analysis stage. The bivariate analysis was conducted using the Kendall's Tau b test to identify the factors that contribute to the risk of stroke and to identify the most influential factors through multivariate analysis using the ANOVA test. Results: The study found that the age risk factor, defined as being over 55 years old, has a score of 2 (high risk) and was present in 28 respondents (46.7%). From the results of the study, it was found that out of 60 respondents, there were 23 respondents (38.3%) who were at moderate risk and 5 respondents (8.3%) who were at high risk of stroke. Conclusion: Respondent characteristics (age and physical activity) are risk factors for stroke in patients with hypertension at the Pagal Health Center. Identification of health behaviors that can be changed remains an important element in preventing stroke, such as maintaining a lifestyle. This study contributes to nursing science, particularly in developing preventive measures for stroke. It enables stroke patients to identify and understand factors that can be anticipated.